Long Term Aging Effects on Polymer Materials Photovoltaic Modules Durability and Safety - Eli Ratih Rahayu; Raihan Raihan; Zinhle Ndlovu; Sondang Visiana Sihotang; Najalia Malika; Anandha Fitriani (International Journal of Cyber ​​and IT Service Management (IJCITSM), 2024)
This study investigates the long term aging effects on polymer materials used in Photovoltaic (PV) modules, with a focus on evaluating their durability, reliability, and safety over extended operational periods. Polymers in PV modules play a critical role in encapsulating and protecting sensitive components from environmental exposure, but they are also subject to degradation due to prolonged exposure to UV radiation, temperature fluctuations, and moisture. This research assesses the aging mechanisms affecting polymer performance, utilizing accelerated aging tests that simulate various environmental conditions to predict material lifespan under real world conditions. Through a combination of thermal, mechanical, and chemical analyses, this study identifies key degradation factors and evaluates their impact on the structural integrity and functionality of PV modules. Findings reveal significant correlations between specific aging stressors and the degradation of polymer materials, which may contribute to efficiency loss and safety risks over time. This study distinguishes itself from existing Technology Acceptance Model (TAM) based e-learning studies by focusing on a comprehensive analysis of polymer degradation mechanisms specific to photovoltaic modules. Unlike prior studies, it evaluates real world conditions through a blend of mechanical, thermal, and chemical analyses, offering unique insights into improving PV system reliability. This research provides insights that can guide manufacturers and engineers in optimizing polymer materials for sustainable and safer PV module applications, particularly in climates with harsh environmental conditions.